Korban Cyberbullying Anak sebagai Korban dalam Pemberitaan Media - Rocky Prayogo; Abraham Ferry Rosando (CV. Era Digital Nusantara, 2023)
Technological progress in Indonesia is very rapid, not only among adults who can feel or enjoy the technological advances in Indonesia, even among children. The existence of technology that is developing rapidly at this time indirectly affects people's lives. Advances in technology make it easier for people to communicate, shop, study, and so on. However, society is very negligent about its own safety in utilizing technology. Technological advances also have a negative impact on society, especially for children who are still studying at the education level. In this digital era, many of us know that it is even normal for bullying to occur on social media, and victims of online bullying (cyberbullying) often occur in children who are not aware of themselves. Therefore, the role of parents is very much needed in terms of supervising children on playing social media. With bullying that is rife on social media, where children become victims of online bullying, it can be fatal if not accompanied continuously. Legal protection for victims must be upheld fairly, regardless of status or race.